Class-I and Class-II Restorations with the Application of a Flowable Composite as an Intermediate Layer—A Narrative Review of Clinical Trials - Anh Duc Nguyen; Kerstin Bitter; Christian Ralf Gernhardt (Journal of Functional Biomaterials)
The objective of this review is to investigate the effect of an additional layer of flowable composite for cavity lining on the clinical outcome of direct posterior composite restorations. The PICO question (patient, intervention, comparison, and outcome) was stated as follows: Does the additional application of a flowable composite as a cavity liner improve the clinical outcome of Class-I and Class-II restorations? The electronic databases MEDLINE, Web of Science, LILAS, and BBO were assessed for identifying relevant clinical studies. After removal of duplicate records, 309 records could be identified and, after a screening of the title and abstract, 20 articles were selected for full-text analysis. Finally, six studies met the eligibility criteria and were included in this review for further investigation. Four of the included studies have a follow-up period of two years, while the other two studies had an observation period of three and seven years, respectively. No significant differences in annual failure rates were observed between restorations with and without a flowable composite liner. Consequently, the additional usage of flowable composites as a cavity liner seems to have no effect on the clinical longevity of direct composite restorations in Class-I and Class-II cavities. Therefore, the application of a flowable composite is a possible option in everyday dental clinical practice.